Pendampingan Destinasi Wisata Aru Jeram Sungai Mararin Lembang Untuk Dijadikan Sumber Penghasilan Bagi Masyarakat Rantedada Tana Toraja Lembang Rantedada - Irengsi Irengsi; Jensi Sanda Pabisa; Helba Rundupadang (BADAN PENERBIT STIEPARI PRESS, 2022)
Lembang Rantedada is one of the lembangs in Mengkendek Timur District, Tana Toraja Regency. Lembang Rantedada is one of the Lembangs that has the potential to be used as a tourist attraction. Therefore, we as PKM UKI TORAJA students are helping the Head of Lembang and the people of Lembang Rantedada to make the village a tourist destination. The first step we took was to create a concept which will later be used as a reference in the continued development of tourist destinations. The aim of this Lembang Rantedada Tourist Destination Concept Design activity is: first, to create public awareness of the importance of utilizing places that have the potential to be used as tourist attractions. Second, provide changes and improvements that are useful for the people of Lembang Rantedada. Third, help the community improve the economy. Fourth, building good relations between PKM students and the community in Lembang Rantedada. The method used in the Lembang Rantedada Tourism Destination Concept Design is to conduct a location survey and also carry out outreach with the local community, and in this concept design we designed it using the AUTOCAD 2017 application. Assistance in the design of the Lembang Rantedada natural tourist destination concept for the Mararin River starting from floor plan, front view, back view, left side view, and right side view. From the front view, starting from the main road entering the river, besides that we see the back view where you can see a gazebo, guest house, parking area and camping site. Then looking to the left we will see a gazebo and also a campsite, looking to the right you can see a bridge crossing to the accommodation and if you look from above we will see the whole of this location. This activity has a good impact on students, namely increasing students' knowledge about how something can be used to gain profits later and also students can gain new experiences regarding good cooperation between communities and for the community, namely as a first step to increasing development, increasing sources of community income and can analyze household expenses by using tourist attractions as a place of income. in Lembang Rantedada. And the local community can improve the economy of the people in Lembang Rantedada. We have high hopes as PKM UKI TORAJA students that with the design of the concept for the natural tourist destination of the Mararin River that we have created a development process.